2002
DOI: 10.1038/nm0602-607
|View full text |Cite
|
Sign up to set email alerts
|

Adult hematopoietic stem cells provide functional hemangioblast activity during retinal neovascularization

Abstract: Adults maintain a reservoir of hematopoietic stem cells that can enter the circulation to reach organs in need of regeneration. We developed a novel model of retinal neovascularization in adult mice to examine the role of hematopoietic stem cells in revascularizing ischemic retinas. Adult mice were durably engrafted with hematopoietic stem cells isolated from transgenic mice expressing green fluorescent protein. We performed serial long-term transplants, to ensure activity arose from self-renewing stem cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
467
3
6

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(490 citation statements)
references
References 35 publications
14
467
3
6
Order By: Relevance
“…Bone-marrow-derived cells have been shown to incorporate sparsely in the endothelium of "normal" blood vessels, reflecting a contribution to physiological endothelial cell turnover, significantly in neovasculature associated with hindlimb ischemia, myocardial infarction, corneal injury, retinal ischemia, cutaneous wounds, grafted aorta segments, and tumor growth. 17,[31][32][33] Few studies have addressed the origin of the renal vasculature. In the past there have been sparse and conflicting reports on the presence of host endothelial cells in kidney allografts.…”
Section: Discussionmentioning
confidence: 99%
“…Bone-marrow-derived cells have been shown to incorporate sparsely in the endothelium of "normal" blood vessels, reflecting a contribution to physiological endothelial cell turnover, significantly in neovasculature associated with hindlimb ischemia, myocardial infarction, corneal injury, retinal ischemia, cutaneous wounds, grafted aorta segments, and tumor growth. 17,[31][32][33] Few studies have addressed the origin of the renal vasculature. In the past there have been sparse and conflicting reports on the presence of host endothelial cells in kidney allografts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in a mouse model of diabetes showed impairment of vasculogenesis in response to hind limb ischemia (Schatteman et al, 2000). Studies in a model of ischemic retinopathy have shown that bone marrow-derived hematopoietic stem cells participate in retinal neovascularization (Grant et al, 2002). Investigations using cell-based gene therapy in the mouse OIR model showed that these cells can rescue and stabilize degenerating vessels, and the cells can inhibit new vessel formation in a mouse model of retinal degeneration (Otani et al, 2002).…”
Section: Vegf and Retinalmentioning
confidence: 99%
“…It has been reported that marrow-derived endothelial progenitor cells contribute to adult vasculogenesis (Tamura et al, 2004) and tumour angiogenesis (Rafii et al, 2002;Peters et al, 2005) by circulating through the vascular system and incorporating into the wall of newly formed vessels (Marchetti et al, 2002;Rafii and Lyden, 2003). Evidence that vasculogenesis is involved in neovascularisation has been found in studies on tumour vessels (Reyes et al, 2002), experimental retinopathy (Grant et al, 2002;Tomita et al, 2004;Butler et al, 2005), myocardial ischaemia (Kocher et al, 2001(Kocher et al, , 2006Botta et al, 2004), wound healing Crisa et al, 1999), and hindlimb ischaemia Kalka et al, 2000;Iwaguro et al, 2002). An important question that remains unanswered by the literature is whether circulating endothelial progenitor cells per se or their differentiated progeny are incorporated into the vascular wall .…”
mentioning
confidence: 99%